Anti-HIV-1 Activity of Weekly or Biweekly Treatment with Subcutaneous PRO 140, a CCR5 Monoclonal Antibody - Jacobson, Jeffrey M. (2010)
BACKGROUND: PRO 140 is a humanized CCR5 monoclonal antibody that has demonstrated potent antiviral activity when administered intravenously to adults infected with CCR5-tropic (R5) human immunodeficiency virus type 1 (HIV-1). This study is the first to evaluate subcutaneous (SC) administration. METHODS: A randomized, double-blind, placebo-controlled study was conducted in 44 subjects with HIV-1 RNA > 5,000 copies/mL, CD4(+) cells > 300/μL, no antiretroviral therapy for ≥12 weeks, and only R5 HIV-1 detectable. Subjects received placebo, 162mg PRO 140, or 324mg PRO 140 weekly for three weeks or 324mg PRO 140 every other week for two doses by SC infusion. Subjects were monitored for 58 days for safety, antiviral effects and PRO 140 serum concentrations. RESULTS: SC PRO 140 demonstrated potent and prolonged antiretroviral activity. Mean log(10) reductions in HIV-1 RNA were 0.23, 0.99 (p=0.0093), 1.37 (p=0.0001), and 1.65 (p<0.0001) for the placebo, 162mg weekly, 324mg biweekly and 324mg weekly dose groups, respectively. Viral loads remained suppressed between successive doses. Treatment was generally well tolerated. CONCLUSIONS: This trial is the first to demonstrate proof of concept for a mAb administered subcutaneously in HIV-1 infected subjects. SC PRO 140 offers the potential for significant dose-dependent HIV-1 RNA suppression and infrequent patient self-administration. TRIAL REGISTRATION: Clinicaltrials.gov register NCT00642707